Arctic shipping and polar seaways - Pic, Pauline; Babin, Julie; Lasserre, Frédéric (Wiley, 2020)
Climate change in the Arctic triggered a series of discourses about the opening-up of a previously unreachable region. Navigation remains however difficult in the Arctic, transits are still very limited, as sea-ice still is a major constraint. How did the development policies of both the North West Passage and the Northern Sea Route unfold ? What are the recent trends in Arctic shipping ? 0